HUBUNGAN PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) DENGAN KEJADIAN STUNTING PADA BALITA USIA 24-60 BULAN DIWILAYAH KERJA PUSKESMAS TANJUNG BUNTUNG KOTA BATAM KEPULAUAN RIAU - Catur Yulinawati; Resi Novia (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
Background : The incidence of stunting in Indonesia is one of the most common diseases in children under five, which is 27.67% caused by several factors and one of the factors is the provision of Complementary Foods (MP-ASI). Objective: This study aims to determine the relationship between complementary feeding and the incidence of stunting in toddlers aged 24-60 months in the Tanjung Buntung Public Health Center, Batam City, Riau Islands. Method: this research is case control, The respondents in this study were 28 people with stunting cases and 28 people who did not experience stunting so that the total was 56 people. Result: Chi-Square test shows that p value = 0.001, OR = 0.133 so that Ho is rejected, this indicates a relationship between complementary feeding (MP-ASI) with the incidence of stunting in Toddlers aged 24-60 months. Conclusion: the incidence of stunting has something to do with the provision of complementary foods for breast milk (MP-ASI). It is recommended for health workers to increase the provision of information and education to parents or mothers of toddlers on the importance of providing nutrition or nutrition needed for toddler growth in an effort to prevent stunting